Industrial Training Report: Perpustakaan Tuanku Bainun Universiti Pendidikan Sultan Idris / Nor Azura Mustafa Bakri - Mustafa Bakri, Nor Azura (Faculty of Information Management, 2018)
The purpose of this documentation is the report regarding to the activities undergone by the practical during the Industrial Training for five months at Perpustakaan Tuanku Bainun, Universiti Pendidikan Sultan Idris. The report is includes the daily task of the task that has be done by the practical students when assigned at library division such as Customer and Circulation Management Division, Academic Support Services and Publicity Division, Administration and Library Automation Division, Acquisition Division and Cataloging Division. In addition, the most important in this report is a special project of practical student in order to get customer's feedback on the effectiveness of information retrieval application (library portal, WebOPAC, iSYS, iPAC, OffPAC). Through industrial training students able manage and improve their communication skill, build self-confidence and be more discipline especially when it involves time management.